Gene conversion in incontinentia pigmenti: a Chinese case series - Lai Ting Leung; Stephanie Ho; Pui Tak Kris Yu; Tsz Shun Myth Mok; Fai Man Ivan Lo; Sze Wing Shirley Cheng; Ho Ming Luk (Journal of Rare Diseases)
Abstract Incontinentia pigmenti (IP) is a rare X-linked dominant condition that leads to variable abnormalities affecting the skin, hair, nails, teeth, eyes, and central nervous system. It is associated with variants in the IKBKG (also known as NEMO) gene, and recent findings have identified gene conversion involving the IKBKG pseudogene (IKBKGP1) as a cause of de novo IP cases in families. This study summarized the clinical features and molecular findings of 47 Chinese IP patients. It is the first published case series to demonstrate somatic gene conversion. We also found that Chinese IP patients have a lower frequency of retinal, dental, hair, nail, and central nervous system abnormalities when compared with IP patients reported overseas. The exons 4–10 deletion of the IKBKG gene was common, but a significant number of patients carried IKBKG variants rarely found in overseas populations, such as c.519 - 3_519 dup. A significant number of cases showed paternal contributory to IP, with some fathers carrying the IKBKGP1 variant and their daughters carrying the IKBKG variant in the same loci, suggesting likely germline gene conversion. There was also a significant proportion of male IP patients in the cohort with only skin involvement. These males either had the IKBKGP1 variant detected in peripheral blood with no IKBKG variant, suggesting possible postzygotic somatic gene conversion confined to localized skin cells or somatic mosaicism. Further studies are required to investigate whether ethnic differences contribute to phenotypic and genotypic variations, to explore possible genotype–phenotype correlations, and to estimate the incidence rate of IKBKGP1 to IKBKG gene conversion in gonadal or somatic cells.